Fragmentation of biomass-templated CaO-based pellets. (1st January 2017) - Erans, María; Cerciello, Francesca; Coppola, Antonio; Senneca, Osvalda; Scala, Fabrizio; Manovic, Vasilije; Anthony, Edward J.
Highlights: Biomass-templated materials using flour as a cheap source of biomass were produced. Fragmentation was tested in PHSR and BFB simulating conditions at calciner entrance. Biomass addition was detrimental to the fragmentation resistance of the particles. This effect was partially neutralised by the inclusion of cement in the production. Results from both PHSR and BFB agreed in terms of behaviour of all particle types. Abstract: The use of biomass templating materials with a cheap production method as an enhanced sorbent for CO2 uptake has been proposed recently. However, the attrition and fragmentation behaviour of this type of material, which is a vital parameter for calcium looping sorbents, has not yet been investigated in detail. In this work the fragmentation behaviour of biomass-templated sorbents is investigated. Three types of materials were prepared using a mechanical pelletiser: 1. lime and cement (LC); 2. lime and flour (LF); and 3. lime, cement and flour (LCF). These samples were heat treated in a pressurised heated strip reactor (PHSR) and in a bubbling fluidised bed (BFB) and changes in particle size distribution were measured to assess fragmentation. Results indicated that the addition of biomass enhances the propensity to undergo fragmentation. Upon heat treatment in the PHSR the particle size of LC was not modified significantly; on the contrary the mean particle diameter of LF decreased from 520 μm to 116 μm and that of LCF from 524 μm to 290 μm. Fragmentation tests in the BFB confirmed the trend: 67% of the particles of LF fragmented, against 53% of LCF and 18% of LC samples. The addition of cement to the LF samples partially counteracts this performance degradation with respect to attrition. However, calcium aluminate pellets (LC) showed the lowest rate of fragmentation amongst all of the samples tested.